Magnetic TFET (MAG-TFET) - Thanet Boonlua; Amporn Poyai; Toempong Phetchakul (2022 International Electrical Engineering Congress (iEECON), 2022)
This paper presents a new structural magnetic field sensor device. The device structure uses the basic structure of tunneling field effect transistor (TFET). The mechanism uses the current-mode Hall phenomenon with tunneling electron carriers from source to drain. The device structure consists of source, gate and drain with two separate contacts on both sides D1 and D2 to accommodate the amount of current difference (∆I D ) caused by Lorentz’s force deflection. The study is carried out by using TCAD simulation. The magnetic field intensity response is linearly dependence. The sensitivity depends on the amount of current and magnetic field intensity. The sensitivity (S) obtained by this device which has width (F w ) 5 nm, length (L g ) 100 nm and height (F h ) 5 nm at biased current of 1000, 100, 10, 1 µA are 0.0133, 0.0263, 0.0812 and 1.22 µA.T -1 respectively. From this experiment, the best relative sensitivity (S R ) is 0.000812 T -1 at 100 µA.
Keywords: Advancements in Semiconductor Devices and Circuit Design; Semiconductor materials and devices; Ferroelectric and Negative Capacitance Devices